Introduction to Mycelium Insulation as a Sustainable Insulation Material and Carbon Sink - Chen Michael Junyou (E3S Web of Conferences)
Climate change is becoming an even bigger threat with the continued production of pollution in the atmosphere. Mycelium insulation offers a potential part of the solution by being a carbon sink and a sustainable material in an otherwise very unsustainable industry of construction and insulation. In this review paper, I present the various materials that can form mycelium insulation, the process of how mycelium insulation is made, and some examples of potential composites that have been studied. Furthermore, I discuss the environmental impact of the insulation industry, and how mycelium insulation can reduce such impacts. Additionally, mycelium insulation is then compared to current alternatives on the market and evaluated by outlining its capabilities across various metrics to determine its performance. I then introduce specific properties of a mycelium composite that can be achieved depending on the substrate make up. Finally, market viability is analysed to show the potential of mycelium insulation. Results show that the current iteration of mycelium insulation may appeal to select individuals that are environmentally conscious, or for specialised cases. Widespread us of mycelium will only be achieved if further innovation occurs or an increase in the need to become environmentally friendly.